Leptospermum extract (QV0) suppresses pleural mesothelioma tumor growth in vitro and in vivo by mitochondrial dysfunction associated apoptosis - Shi, Huaikai; Zhang, Le; Yu, Ta-Kun; Zhuang, Ling; Ke, Helen; Johnson, Ben; Rath, Emma; Lee, Kenneth; Klebe, Sonja; Kao, Steven; Qin, Karl Lijun; Pham, Hong Ngoc Thuy; et al. (Frontiers in Oncology, 2023)
Pleural mesothelioma (PM) is a highly aggressive, fast-growing asbestos-induced cancer with limited effective treatments. There has been an interest in using naturally occurring anticancer agents derived from plant materials for the treatment of PM. However, it is unclear if aqueous extract from the Leptospermum polygalifolium (QV0) has activity against PM. Here we investigated the anti-cancer properties of QV0 and Defender® (QV0 dietary formula) in vitro and in vivo, respectively. QV0 suppressed the growth of 8 PM cell lines in a dose-dependent manner, effective at concentrations as low as 0.02% w/v (equivalent to 0.2mg/ml). This response was found to be associated with inhibited cell migration, proliferation, and colony formation, but without evident cell cycle alteration. We observed mitochondrial dysfunction post QV0 treatment, as evidenced by significantly decreased basal and maximal oxygen consumption rates. Ten SCID mice were treated with 0.25mg/g Defender® daily and exhibited a reduced tumour size over 30 days, which was associated with an average extension of seven days of mouse life. There was no evidence of liver toxicity, nor increased blood glucose post-treatment in animals treated with Defender®. Significantly enhanced tumour apoptosis was observed in the Defender®-treated animals, correlating with mitochondrial dysfunction. Lastly, the high level of polyphenols and antioxidant properties of QV0 and Defender® were detected in HPLC analysis. To the best of our knowledge, this study constitutes the first demonstration of an improved host survival (without adverse effects) response in a QV0-treated PM mouse model, associated with an evident inhibition of PM cell growth and mitochondrial dysfunction-related enhancement of tumour apoptosis.